Surplus Crop Residues for Energy Generation in Selected Districts of Madhya Pradesh - An Assessment - De, Dipankar (Journal of Agricultural Engineering, 2008)
Crop residues are one of the promising resources in rural India for energy generation. Crop residues in combine harvested fields are burnt in situ in many parts of the country. Alternate uses of such residues for energy generation can mitigate the loss of material and environment pollution caused by field burning. The study undertaken in six districts of Madhya Pradesh for assessment of crop residue production and uses indicated that among the food grains crops cultivated, the crop residues from manually harvested fields were mainly used as animal feeds. Residues from crops like cotton, pigeon pea, mustard were used for domestic purposes. Soybean and wheat crop residues in combine harvested fields were prone to disposal through field burning, the extents depending upon the productivity, cropping intensity, labour and storage space availability. Among the six districts, Bari Block (Raisen district) had the highest (1361 kg/ha) crop residue so generated with 76% of it being burnt. In Budni and Nasrullaganj Blocks (Sehore district), 60-67% of 812 kg/ha and 753 kg/ha of crop residues were burnt. About 1.05 lakh tonnes of crop residues (wheat 74.3% soybean 25.7%) were burnt annually in the three blocks and have potential of generation of 305.6 TJ of energy. For decentralised electricity generation through gasification route, a cluster of 7 villages can support feedstock requirement of a 90 kWe gasifier system to operate for 300 days in a year operating at 12h/day.